Heterotrimeric Gi Proteins link Hedgehog signaling to activation of Rho small GTPases to promote fibroblast migration - Polizio, Ariel Héctor (2011)
Evidence supporting the functionality of Smoothened (SMO), an essential transducer in most pathways engaged by Hedgehog (Hh), as a Gi-coupled receptor contrasts with the lack of an apparently consistent requirement for Gi in Hh signal transduction. In the present study, we sought to evaluate the role of SMO-Gi coupling in fibroblast migration induced by Sonic Hedgehog (Shh). Our results demonstrate an absolute requirement for Gi in Shh-induced fibroblast migration. We found that Shh acutely stimulates the small Rho GTPases Rac1 and RhoA via SMO through a Gi protein- and PI3K-dependent mechanism, and that these are required for cell migration. These responses were independent of transcription by Gli and of the C-terminal domain of SMO, as we show using a combination of molecular and genetic tools. Our findings provide a mechanistic model for fibroblast migration in response to Shh and underscore the role of SMO-Gi coupling in non-canonical Hh signaling.